Optical properties of B2O3–CaF2 glass-ceramics doped with silver nanoparticles and praseodymium ions - Naranjo, Luz Patricia; Oliveira, Nathália Talita C.; Kassab, Luciana R.P. [UNESP]; de Araújo, Cid B. (Elsevier, 2021)
We report on the synthesis and optical experiments with borate glass-ceramics (B2O3–CaF2 glass enclosing CaF2 nanocrystals), either undoped or doped with praseodymium ions (Pr3+) and containing silver nanoparticles (Ag-NPs). The techniques of transmission electron microscopy, X-rays diffraction, linear optical absorption, and photoluminescence (PL), were used to characterize the samples prepared. The glass samples, prepared by using the diffusion method, were heat-treated for nucleation of CaF2 nanocrystals (CaF2–NCs) with cubic structure and dimensions of ~20 nm, and Ag-NPs (with sizes between ~2 and ~50 nm). Optical absorption and PL experiments were performed. The glass-ceramic with Ag-NPs, but without Pr3+, exhibited tenfold enhancement (~1000%) of the blue PL from the CaF2–NCs, in comparison with the samples without Ag-NPs. In the samples with Pr3+ the presence of Ag-NPs induced small enhancement of the absorption spectra in the blue region [Pr3+ transitions: 3H4→3PJ (J = 0, 1, 2), 1I6] and 75% increase of the emitted intensity in the red region (Pr3+ transitions: 1D2→3H4). On the other hand, the CaF2–NCs luminescence was totally quenched due to the presence of Pr3+. This effect was attributed to resonant energy-transfer from the CaF2–NCs to Pr3+. The phenomena observed in the experiments were understood considering the contributions of the local electric field in the vicinities of the Ag-NPs and processes of energy-transfer among the CaF2–NCs, Ag-NPs and Pr3+.
Keywords: B2O3–CaF2 glasses; Borate glass-ceramics; CaF2 nanocrystals; Pr3+ions; Silver nanoparticles